2022
DOI: 10.3390/ijms23147547
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Localized Administration of α-GalCer to Recruit Invariant Natural Killer T Cells and Enhance Their Antitumor Activity against Solid Tumors

Abstract: Invariant natural killer T (iNKT) cells have the capacity to mount potent anti-tumor reactivity and have therefore become a focus in the development of cell-based immunotherapy. iNKT cells attack tumor cells using multiple mechanisms with a high efficacy; however, their clinical application has been limited because of their low numbers in cancer patients and difficulties in infiltrating solid tumors. In this study, we aimed to overcome these critical limitations by using α-GalCer, a synthetic glycolipid ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…However, the production of IFN-γ by iNKT and other lymphocytes was essential for protection. Using humanised NSG mice, a recent study showed that tumour localised administration of αGalCer can significantly enhance iNKT cell-mediated anti-tumour capacity against solid tumours ( 75 ).…”
Section: Preclinical Studies: Inkt Cells In Cancermentioning
confidence: 99%
“…However, the production of IFN-γ by iNKT and other lymphocytes was essential for protection. Using humanised NSG mice, a recent study showed that tumour localised administration of αGalCer can significantly enhance iNKT cell-mediated anti-tumour capacity against solid tumours ( 75 ).…”
Section: Preclinical Studies: Inkt Cells In Cancermentioning
confidence: 99%
“…Recent investigations have included the application of human iNKT cells transferred to humanized mice with tumors, along with direct α-GalCer administration into these tumors. These studies revealed a robust and rapid recruitment of iNKT cells, resulting in effective anti-tumor effects [203].…”
Section: Current Advances In Inkt-mediated Cancer Immunotherapymentioning
confidence: 99%
“…Human invariant natural killer T (iNKT) cells treated with α‐GalCer showed significantly increased efficacy in tumor‐bearing NSG mice, but the dose of α‐GalCer was related to the efficacy and safety of iNKT cell therapy (Y.‐R. Li et al, 2022). Furthermore, blocking the functional C–C'loop region of a V‐domain Ig suppressor of T‐cell activation to reduce inhibition of myeloid‐derived T cell activity and prevented neutrophil migration (Thakkar et al, 2022).…”
Section: Cancer Treatment Based On Humanized Micementioning
confidence: 99%
“…. Human invariant natural killer T (iNKT) cells treated with α-GalCer showed significantly increased efficacy in tumor-bearing NSG mice, but the dose of α-GalCer was related to the efficacy and safety of iNKT cell therapy (Y.-R Li et al, 2022)(Thakkar et al, 2022).…”
mentioning
confidence: 99%